CD20 alternative splicing isoform generates immunogenic CD4 helper T epitopes. Issue 1 (12th December 2014) - Vauchy, Charline; Gamonet, Clementine; Ferrand, Christophe; Daguindau, Etienne; Galaine, Jeanne; Beziaud, Laurent; Chauchet, Adrien; Henry Dunand, Carole J.; Deschamps, Marina; Rohrlich, Pierre Simon; Borg, Christophe; Adotevi, Olivier; et al.
Abstract : Cancer‐specific splice variants gain significant interest as they generate neo‐antigens that could be targeted by immune cells. CD20, a membrane antigen broadly expressed in mature B cells and in B cell lymphomas, is subject to an alternative splicing named D393‐CD20 leading to loss of membrane expression of the spliced isoform. D393‐CD20 expression is detectable in transformed B cells and upregulated in various lymphoma B cells. In this study, we show that D393‐CD20 is translated in malignant B cells and that D393‐CD20 specific CD4 T cells producing IFN‐γ are present in B‐cell lymphoma patients. Then, we have investigated whether the 20mer D393‐CD20 peptide spanning the splicing site might be targeted by the immune system and we have shown that D393‐CD20‐specific CD4 Th1 clones could directly recognize malignant B cell lines and kill autologous lymphoma B cells indicating that D393‐CD20‐derived epitopes are naturally processed and presented on tumor cells. Finally, D393‐CD20 peptide‐based vaccination induced specific CD8 and CD4 T cell responses in HLA‐humanized transgenic mice suggesting the presentation of D393‐CD20 derived peptides on both HLA Class‐I and ‐II. These findings support further investigations on the potential use of D393‐CD20 directed specific immunotherapy in B cell malignancies. Abstract : What's New? Cancer‐specific splice variants are generating interest as they may potentially be used as biomarkers and generate novel targets for therapy. Here, the authors investigate whether an alternative transcript of the B cell lineage membrane receptor CD20 could generate epitopes that are recognized by T lymphocytes and eligible as new targets for immunotherapy. They show that D393‐CD20 generates promiscuous HLA‐DR epitopes recognized by CD4 T cells, and that naturally occurring D393‐CD20‐specific T cells are present in B cell lymphoma patients. The findings support further studies on the modulation of D393‐CD20‐specific T cell response by Rituximab and the development of D393‐CD20‐specific immunotherapies.